Factors Related to the Used of Electric Cigarette Behavior in Vapers Community in Kupang - Alfin Savitra Umar; Marselinus Laga Nur; Honey Ivone Ndoen (Universitas Nusa Cendana, 2023)
The World Population Review in 2021 show that smoking rates are highest in Southeast Asia and South Asia and tend to be very high in men compared to women. Kiribati has the highest smoking rate in the world with 52.40% and Indonesia has smoking rate 39.90%. The results of Riskesdas in 2018 show that the number of active smokers every day in Indonesia is 24.3% and NTT Province is ranked 19th as the province with the highest proportion of the population smoking and chewing tobacco with a percentage of 11.7%. E-cigarettes can cause addiction. The American FDA conducted a study on the liquid content of e-cigarettes which stated that e-cigarettes contain Tobacco Specific Nitrosamine (TSNA) which is toxic and Diethylene Glycil (DEG) or as carcinogens. Factors related to the use of e-cigarettes are peer interaction factors, family members who use e-cigarettes, cigarette advertisements, and lifestyle. This study aims to determine the description of the determinants that affect the use of e-cigarettes in the Kupang Vapers community in 2021. This research method is a descriptive study using a cross sectional design. This research was carried out from March to April 2021. The sample was 80. The data analysis used was univariate. The results of this study indicate that most respondents have a good level of knowledge, have an accepting attitude, have good actions, have a high income level, have available facilities and infrastructure, have family members who smoke, respondents are not affected by cigarette advertisements, and are not influenced by peers.